2018
DOI: 10.1007/s40520-018-0938-5
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of reduced walking speed using simple measurements of physical and psychophysiological function in community-dwelling elderly people: a cross-sectional and longitudinal study

Abstract: The results of this study suggest that MSL may serve as a simple surrogate indicator of UWS in elderly people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The present findings confirmed those coming from another systematic review suggesting that the combination of various spatio-temporal parameters of gait may enhance the sensitivity and specificity of frailty risk prediction and classification. 30 Adachi and colleagues 126 showed how maximum step length also showed good predictive accuracy for usual walking speed < 0.8 m/s. Recently, Grande and colleagues, 127 in another review article, summarized the evidence concerning the association of slow gait speed with cognitive decline and dementia and discussed the possible shared pathways leading to cognitive and motor impairments, under the unifying hypothesis that body and mind are intimately connected.…”
Section: Discussionmentioning
confidence: 98%
“…The present findings confirmed those coming from another systematic review suggesting that the combination of various spatio-temporal parameters of gait may enhance the sensitivity and specificity of frailty risk prediction and classification. 30 Adachi and colleagues 126 showed how maximum step length also showed good predictive accuracy for usual walking speed < 0.8 m/s. Recently, Grande and colleagues, 127 in another review article, summarized the evidence concerning the association of slow gait speed with cognitive decline and dementia and discussed the possible shared pathways leading to cognitive and motor impairments, under the unifying hypothesis that body and mind are intimately connected.…”
Section: Discussionmentioning
confidence: 98%
“…However, the risk of bias was uncertain for both models. Both models were evaluated in the same cohort by Adachi et al, which observed that a gait speed of <0.8m/s had an excellent discrimination (c statistic 0.91), and a gait speed of <1.0m/s had a good discrimination (c statistic 0.89) for the outcome mobility limitations at two years follow-up [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies included other tests [41,69,91] to assess the predictive validity on mobility limitations, disability, and frailty.…”
Section: Other Testsmentioning
confidence: 99%